2011
DOI: 10.1175/2011jcli3672.1
|View full text |Cite
|
Sign up to set email alerts
|

Tropical and Subtropical Cloud Transitions in Weather and Climate Prediction Models: The GCSS/WGNE Pacific Cross-Section Intercomparison (GPCI)

Abstract: A model evaluation approach is proposed in which weather and climate prediction models are analyzed along a Pacific Ocean cross section, from the stratocumulus regions off the coast of California, across the shallow convection dominated trade winds, to the deep convection regions of the ITCZ-the Global Energy and Water Cycle Experiment Cloud System Study/Working Group on Numerical Experimentation (GCSS/ WGNE) Pacific Cross-Section Intercomparison (GPCI). The main goal of GPCI is to evaluate and help understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 87 publications
7
128
0
Order By: Relevance
“…Strong (poor) spatial correspondence between radiance skewness and AIRS ECF (MODIS cloud fraction) was found, suggesting infraredbased ECF is a potentially valuable and unappreciated diagnostic for MBL cloud characterization. The mean MBL depth derived from AIRS (Martins et al, 2010) shows a characteristic transition from shallow MBLs (920-970 hPa) near the coast to deeper MBLs (830-880 hPa) away from the coast and is a well-observed feature of the stratocumulus-tocumulus transition (e.g., Teixeira et al, 2011). The AIRSderived dMSE between 700 and 1000 hPa agree very well with ERA-Interim (Kubar et al, 2012).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Strong (poor) spatial correspondence between radiance skewness and AIRS ECF (MODIS cloud fraction) was found, suggesting infraredbased ECF is a potentially valuable and unappreciated diagnostic for MBL cloud characterization. The mean MBL depth derived from AIRS (Martins et al, 2010) shows a characteristic transition from shallow MBLs (920-970 hPa) near the coast to deeper MBLs (830-880 hPa) away from the coast and is a well-observed feature of the stratocumulus-tocumulus transition (e.g., Teixeira et al, 2011). The AIRSderived dMSE between 700 and 1000 hPa agree very well with ERA-Interim (Kubar et al, 2012).…”
Section: Discussionsupporting
confidence: 60%
“…MERRA is on average moister than AIRS by ∼ 5 % in the NH, nearly identical to AIRS in the SEA, and a much more spatially heterogeneous difference is observed in the SEP from the coastal proximity westward between 8 and 12 • S. Bretherton et al (2010) demonstrate that the free troposphere in the SEP westward of 75 • W is characteristically very dry (0.1 g kg −1 ) with sporadic filaments of moist air (as high as 3-6 g kg −1 ) up to an altitude of 2.5 km. In addition, these moist filaments have been observed with GPS-RO refractivity profiles by von Engeln et al (2007). The vertical structure of RH obtained from VOCALS-REx radiosondes implies a well-mixed MBL near the coast with MBL decoupling west of 80 • W. Myers and Norris (2015) showed that 700 hPa is drier in the SH subtropics than in the NH using ERA-Interim data.…”
Section: Regional Spatial Averagesmentioning
confidence: 82%
“…The typical characteristic that the cloud layers are lower near California than near Peru is also well captured in the data. Karlsson et al (2010) showed cloud-top-height evolution along the GPCI line (GCSS/WGNE Pacific cross-section intercomparison; GCSS: GEWEX cloud system study; WGNE: working group on numerical experimentation; GEWEX: Global Energy and Water Exchanges Project; see Teixeira et al 2011) off California using Multi-angle Imaging SpectroRadiometer (MISR) data. Stratocumulus cloud structure along 20°S observed by a cloud radar and upward-pointing lidar aboard an aircraft is shown in Bretherton et al (2010), Rahn and Garreaud (2010), and Abel et al (2010).…”
Section: Basic Features Of the Data A Boundary Layer Cloudsmentioning
confidence: 99%
“…4 CGILS focuses on three cases of boundary-layer clouds occurring along a transect ranging from California to Hawaii (Teixeira et al 2011) and representative of stratus, stratocumulus and shallow cumulus cloud types (Karlsson et al 2010). For each case, idealized large-scale conditions representative of the present-day climate are derived from European Centre for Medium-Range Weather Forecasts (ECMWF) analysis, and idealized large-scale forcings representative of global warming conditions are derived by prescribing a ?2 K SST increase and by assuming that the tropical temperature profile follows a moist adiabat, that the relative humidity remains constant, that profiles of horizontal heat and moisture advection are unchanged, and that large-scale subsidence is changed so as to balance the radiative cooling above the boundary layer (Zhang and Bretherton 2008).…”
Section: Idealized Single-column Simulationsmentioning
confidence: 99%